Proceedings of the 2007 ACM SIGMETRICS International Conference on Measurement and Modeling of Computer Systems 2007
DOI: 10.1145/1254882.1254919
|View full text |Cite
|
Sign up to set email alerts
|

Clustering and sharing incentives in BitTorrent systems

Abstract: Peer-to-peer protocols play an increasingly instrumental role in Internet content distribution. Consequently, it is important to gain a full understanding of how these protocols behave in practice and how their parameters impact overall performance. We present the first experimental investigation of the peer selection strategy of the popular BitTorrent protocol in an instrumented private torrent. By observing the decisions of more than 40 nodes, we validate three BitTorrent properties that, though widely belie… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
71
0

Year Published

2007
2007
2015
2015

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 183 publications
(73 citation statements)
references
References 17 publications
2
71
0
Order By: Relevance
“…Legout et al [3] showed that the clustering produced by the choking algorithm favors leechers with higher upload bandwidth. The malicious leecher 3 perturbs the clustering produced by the choking algorithm.…”
Section: Attack Details and Experimental Evaluationmentioning
confidence: 99%
See 1 more Smart Citation
“…Legout et al [3] showed that the clustering produced by the choking algorithm favors leechers with higher upload bandwidth. The malicious leecher 3 perturbs the clustering produced by the choking algorithm.…”
Section: Attack Details and Experimental Evaluationmentioning
confidence: 99%
“…Good clustering ensures that the leechers with high upload bandwidth are rewarded with higher download rates and they are able to complete their downloads more quickly. Finally, the choking algorithm has been shown to converge towards good clustering shortly after the beginning of the download [3]. We refer interested readers to [1] for a detailed description of the choking algorithm.…”
Section: Introductionmentioning
confidence: 99%
“…Prima facie, the notion of coalition described above appears similar to that of clusters studied in [14], where a cluster is defined to be a set of peers with similar upload capacities. However, the clusters studied in [14] are formed as a consequence of the selfish nature of peers and of using the Tit-for-Tat strategy.…”
Section: Introductionmentioning
confidence: 99%
“…However, the clusters studied in [14] are formed as a consequence of the selfish nature of peers and of using the Tit-for-Tat strategy. Unlike a coalition, there is no explicit cooperation among peers in a cluster.…”
Section: Introductionmentioning
confidence: 99%
“…Other solutions have focused on improving the piece selection algorithm, at the seed (source of the content) [5]- [7] or for all peers [8] showing improvements with respect to, e.g., the classical BitTorrent protocol [9], either in static [8] or in dynamic overlays [6], [7]. An alternative line of work has focused instead on characterizing the swarming effects by measurement studies [10], [11], and by modeling the behavior of swarming protocols [12], [13]. These analytical results assume that peersets are static, and their analysis is at the steady state.…”
Section: Introductionmentioning
confidence: 99%